Distribution and genetic diversity of adeno-associated viruses in bats from coastal areas of Southeast China - Zhu, Changqiang (Sci Rep, 2020)
Bats are associated with several important zoonotic viruses from different families. One example includes adeno-associated viruses (AAVs), that are extensively detected in several animals, especially primates. To understand AAVs distribution and genetic diversity in the coastal areas of Southeast China, a total of 415 intestine samples were mostly collected from two provinces of southeast China, i.e., Zhejiang and Fujian province. Intestine samples from five bat species were collected for AAVs detection. The average prevalence rate for AAV detection among these samples was 18.6% (77 positives out of 415 samples) and ranged from 11.8 to 28.9% between the five bat species. This suggests that AAVs are widely distributed in diverse bat populations in southeast coastal areas of China. Based on the genome sequence of bat adeno-associated virus-CXC1(BtAAV-CXC1) from one AAV-positive sample, the genetic diversity of the detected AAVs were assessed and analyzed. Phylogenetic analysis revealed that BtAAV-CXC1 was comparatively distant to other major AAVs from mammals and non-mammals, with only a 52.9~64.7% nucleotide identity. However, they were phylogenetically closer to Rhinolophus sinicus bat adeno-associated virus (Rs-BtAAV1), with a 74.5% nt similarity. Partial analysis of the rep and cap overlapping open reading frame (ORF) sequences from bat AAV samples revealed 48 partial rep sequences and 23 partial cap sequences from positive samples shared 86.9 to 100% and 72.3 to 98.8% nucleotide identities among themselves, respectively. This suggests that the detected AAVs had a distinctly high genetic diversity. These findings led us to conclude that diverse AAVs may be widely distributed in bat populations from the southeast regions of China.